Obesity- attributable costs of absenteeism among working adults in Portugal - Kelli Destri; Joana Alves; Maria João Gregório; Sara Simões Dias; Ana Rita Henriques; Nuno Mendonça; Helena Canhão; Ana Maria Rodrigues (BMC, 2022)
Abstract Background Obesity leads to poor health outcomes and may adversely affect work productivity. This study, aimed to investigate the obesity- attributable costs of absenteeism among working adults in Portugal. Methods The study population included individuals actively working at baseline from the Epidemiology of Chronic Diseases Cohort (EpiDoC), a large Portuguese population-based prospective study. Body mass index was measured at baseline and in two follow-up interviews. Absenteeism in each wave of the EpiDoC was assessed by the question "Did you have a sick leave in the previous 12 months? yes/no", followed by "How many days did you miss work due to sickness in the previous twelve months?". Body mass index (BMI) was classified into underweight, normal weight, overweight, and obese, based on the standard World Health Organization definition. Association between obesity and absenteeism was estimated with the negative binomial regression model adjusted for BMI, chronic diseases, and lifestyle. Obesity- attributable costs were calculated using lost gross income during the time absent from work, through the human-capital approach. Results The EpiDoC included 4338 working adults at baseline. Of these, 15.2% were obese at the beginning of the study and 22.7% of the population had been absent from work in the last 12 months. Participants with obesity missed 66% more days at work (IRR: 1.66; CI 95%:1.13-2.44; (p = 0.009.) than those with normal weight. The odds of having been absent from work were 1.4 times higher in obese compared to non-obese individuals (CI 95%: 1.18-1.67; p < 0.01) adjusted to sex and type of work. Obese individuals missed 3.8 more days per year than those with normal weight (95%CI: 3.1-4.5). Extrapolating to the entire Portuguese working population, absenteeism due to obesity incurred an additional cost of €238 million per year. Conclusion Obesity imposes a financial burden due to absenteeism in Portugal. Employers and national health regulators should seek effective ways to reduce these costs.